Oxidative Stress Signaling in Blast TBI-Induced Tau Phosphorylation - Chunyu Wang; Changjuan Shao; Li Zhang; Sandra L. Siedlak; James S. Meabon; Elaine R. Peskind; Yubing Lu; Wenzhang Wang; George Perry; David G. Cook; Xiongwei Zhu (MDPI AG, 2021)
Traumatic brain injury caused by blast is associated with long-term neuropathological changes including tau phosphorylation and pathology. In this study, we aimed to determine changes in initial tau phosphorylation after exposure to a single mild blast and the potential contribution of oxidative stress response pathways. C57BL/6 mice were exposed to a single blast overpressure (BOP) generated by a compressed gas-driven shock tube that recapitulates battlefield-relevant open-field BOP, and cortical tissues were harvested at different time points up to 24 h after blast for Western blot analysis. We found that BOP caused elevated tau phosphorylation at Ser202/Thr205 detected by the AT8 antibody at 1 h post-blast followed by tau phosphorylation at additional sites (Ser262 and Ser396/Ser404 detected by PHF1 antibody) and conformational changes detected by Alz50 antibody. BOP also induced acute oxidative damage at 1 h post-blast and gradually declined overtime. Interestingly, Extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) were acutely activated in a similar temporal pattern as the rise and fall in oxidative stress after blast, with p38 showing a similar trend. However, glycogen synthase kinase-3 β (GSK3β) was inhibited at 1 h and remained inhibited for 24 h post blast. These results suggested that mitogen-activated protein kinases (MAPKs) but not GSK3β are likely involved in mediating the effects of oxidative stress on the initial increase of tau phosphorylation following a single mild blast.